Managing perceived challenges of e-learning in Nigerians higher education (2012)
Higher education is the climax of the process of providing knowledge, changing learners attitude and inculcating specialized skills in individuals preparatory to taking a life- long employment with intent to earning a living and equally contributing to national economic growth and development. The teaching and learning process is cardinal to the realization of the educational objectives of any nation. The advent of information and communication technology has made teaching and learning easier and beyond the traditional face to face interaction between the teacher and the learner. E-learning basically involving the transfer of skills and knowledge through an electronic device aims at improving the teacher/ learning process. In spite of the benefits of e-learning to both regular students distance learners, e-learning has been fraught with some challenges in Africa. Therefore, this paper discusses some of the challenges facing e-learning in Africa paarticularly in the Nigerian higher education system. These among others are epileptic power supply, high cost of procurement of computer hardware, inadequate infracture, and resistence to change on the part of the instructors, inability of learners to make use of ICT infracture, inadequate skilled manpower ICT, and corruption of computer storage device through viruses. Effectively managing the identified challenges means that the government would have to ensure regualr power supply, lecturers and learners should be trained in the use of ICT infrastructure, and the government should evolve viable ICT policy as well as control or subsidies the price of the ICT infrastructure to make it affordable for both lectures and learners.